Gap analysis for the facilities management services in Malaysian Government office buildings - Majid, Noor Azizah; Muhamad Ariff, Nor Rima; Ismail, Faridah; Mohd Tobi, Siti Uzairiah (UiTM Press, 2025)
The Malaysian Government is increasingly using Facility Management (FM), and it is becoming more widely accepted and popular within the Ministry. Implementing Facility Management (FM) in Malaysia aims to enhance the systematic maintenance of government facilities, thereby extending the lifespan of the building structure. Implementing Facility Management ensures the property's maintenance and prolongs the asset's lifespan. However, the extent to which this service has met the end user's needs is still yet to be determined. Ensuring that the service provider's performance reaches the necessary standard is essential. An enhancement can be executed. This article examines the quality of FM services in government office buildings in Malaysia. This research aims to discover discrepancies between end-user expectations and perceptions of facilities management services using the five elements of the SERVQUAL model: reliability, responsiveness, assurance, empathy, and tangibles. 152 endusers from government office buildings took part in this study. The survey results revealed that service quality gaps in facilities management services are indeed occurring. Therefore, it can be concluded that perceptions of the service are below user expectations, highlighting the need for significant improvements to boost service quality. This study will benefit all parties involved in creating documentation and overseeing the implementation of the FM contract. bservation.